Energy, exergy, environment and economic (4E) analysis of PV/T module assisted vapor compression refrigeration system: An experimental study - Yildiz, Gokhan; Gurel, Ali Etem; Katircioglu, Ferzan; Agbulut, Umit (CELL PRESS, 2024)
Despite the rise in the prices of fossil fuels, the increase in their demand, and damaging the environment, a large part of the world's energy needs have been today met by fossil fuels. In this direction, interest in renewable energy sources has increased. Solar energy stands out among renewable energy sources because it is endless and clean. However, today, the use of solar energy is not used alone, but in combination with other thermal energy systems. In building applications, it is mostly used in heating, refrigeration, and HVAC systems, which have a high part in energy consumption. In this study, the solar energy and cooling system were not used separately as in previous studies but were used as a hybrid. The focus was on increasing the performance of both systems by operating them together. In this study, energy, exergy, thermoeconomic, and environmental analyses were applied to the PV/T-assisted vapor compression refrigeration system (PV/T-VCRS) at different storage temperatures (25 degrees C, 30 degrees C, and 35 degrees C). As a result, an 8.5 % lower surface temperature of the module in PV/T-VCRS 25 degrees C was measured compared to PV/T-VCRS 30 degrees C and 35 degrees C. In direct proportion to the module surface temperatures, 13 % better electrical efficiency was obtained in PV/T-VCRS 25 degrees C compared to 30 degrees C and 35 degrees C. The COP value increased by 15.46 % in PV/T-VCRS 25 degrees C compared to 30 degrees C and 35 degrees C. A 13 % improvement in exergy efficiency was observed in PV/T-VCRS 25 degrees C compared to 30 degrees C and 35 degrees C. The enviroeconomic parameter PV/T-VCRS is calculated as 15.17 cent/h, 16.52 cent/h, and 17.6 cent/h for 25 degrees C, 30 degrees C and 35 degrees C. Another advantage of the system is that hot water is obtained at set temperatures. In PV/T-VCRS, 475 L, 300 L, and 210 L of hot water were obtained at 25 degrees C, 30 degrees C, and 35 degrees C, respectively. As a result, the performance of the PV/T-VCRS was good, with the added benefit of performing close to the performances when PV/T and VCRS were used separately.
Keywords: Thermodynamic analysis; Photovoltaic/thermal module; Vapor compression refrigeration system; Superheating; HEAT-PUMP SYSTEM; PERFORMANCE EVALUATION; RENEWABLE ENERGY; SOLAR; TEMPERATURE; COLLECTOR; STORAGE; POWER; Science & Technology - Other Topics